The teachers' obstacles in implementing technology in mathematics learning classes in the digital era - Muhazir, A; Retnawati, H (Journal of physics. Conference series, 2020)
The use of technology in mathematics teaching-learning has been proven to be successful in increasing students' motivation, interests, and achievement. However, the use of technology in learning mathematics in answering the challenges of the digital era has not been successfully implemented as a whole with only 19.22% at the junior high school level and even at the senior high school level only 16.23%. Teacher professionalism is not enough to guarantee the implementation of technology in mathematics education. Unequal facilities and infrastructure are also obstacles. This research aims to describe the obstacles of mathematics teachers in applying technology in mathematics teaching-learning. This research is a case study research with the subject of 12 mathematics teachers in South Kalimantan, Indonesia. Data were collected using questionnaires and interviews. Data analysis was done using the Miles & Huberman model, with the step of data reduction, data display, and conclusion. The results showed that the obstacles of mathematics teachers in the digital era in implementing technology in mathematics teaching-learning included: (1) mathematics learning material that was less suitable for the use of technology; (2) facilities, infrastructure, and support provided by schools were inadequate for the use of technology in teaching-learning; (3) the level of teacher skills in using technology in mathematics teaching-learning. Some factors that influenced the emergence of these obstacles include (1) teachers assessments and point of views of the effectiveness in using technology in teaching-learning mathematics in the classroom; (2) unequal access to education services between schools in cities and villages; and (3) lack of training and information provided to the teachers about the use of technology in mathematics classes. Those obstacles obtained were common obstacles experienced by the teachers in South Kalimantan, Indonesia, both in urban and rural environments.